Pelatihan Komputer Microsoft Office dan Media Pembelajaran Animasi untuk Meningkatkan Kompetensi Guru SDIT Al Muhajirin - Endi Permata; Yus Rama Denny M; Irwanto; Mohammad Fatkhurrokhman (Universitas Lancang Kuning, 2021)
This community service activity aims to increase the competence of information and communication technology (ICT) through Microsoft Office computer training and animation learning media at the Al Muhajirin Integrated Islāmic Elementary School, Cilegon, Banten. The output of this program has an impact on the creation of teachers who are skilled in using technology in learning, trained teachers who are able to use technology especially Microsoft Office and learning animation media. In this training, DIT Al Muhajirin Cilegon Banten teachers were trained on Microsoft office and the theory and principles of animation as a learning medium. Furthermore, the training continued with intensive mentoring of the SDIT Al Muhajirin Cilegon Banten teacher to choose themes and practices for making learning animations. With the training held at SDIT Al Muhajirin Cilegon Banten, this primary school teacher who became a participant in community service has achieved this understanding of the benefits of sustainable professional development in teacher performance assessment. Teachers are able to master how to make animation media for learning using PowerPoint Microsoft Teachers at SDIT Al Muhajirin Cilegon Banten who are community service participants are trained to understand the features and functions in Microsoft PowerPoint which are used for making animation media in learning. From the results of community service activities carried out at SDIT Al-Muhajirin Cilegon Banten, it can be concluded that the assessment of the ability of participants on average is around 84.15% and have mastered and understood Microsoft office materials and learning animations.